2018
DOI: 10.1016/j.addbeh.2017.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from adequate to inadequate sleep duration associated with higher smoking rate and greater nicotine dependence in a population sample

Abstract: Introduction Inadequate sleep (≤6 and ≥9 h) is more prevalent in smokers than non-smokers but the extent to which sleep duration in smokers relates to smoking behaviors and cessation outcomes, is not yet clear. To begin to address this knowledge gap, we investigated the extent to which sleep duration predicted smoking behaviors and quitting intention in a population sample. Methods Data from current smokers who completed the baseline (N=635) and 5-year follow-up (N=477) assessment in the United Kingdom Bioba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…This increased prevalence in people with mental illness is attributed to several factors including disparities in access to tobacco cessation programs, lower socioeconomic status, and increased rates of stressful life events (Prochaska et al, 2017). Our results are also consistent with prior studies showing smoking to be associated with increased risk for suicidal behavior, suicide, and with increased aggression, impulsivity, and poor sleep (Bloom et al, 2013;Dakwar et al, 2011;Miller et al, 2000aMiller et al, , 2000bMitchell, 1999;Oquendo et al, 2004;Patterson et al, 2018;Poorolajal and Darvishi, 2016). Furthermore, aggression, impulsivity, and poor sleep are risk factors for suicidal behavior (Carli et al, 2010;Goldstein et al, 2008;Melhem et al, 2007;Nock and Kessler, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…This increased prevalence in people with mental illness is attributed to several factors including disparities in access to tobacco cessation programs, lower socioeconomic status, and increased rates of stressful life events (Prochaska et al, 2017). Our results are also consistent with prior studies showing smoking to be associated with increased risk for suicidal behavior, suicide, and with increased aggression, impulsivity, and poor sleep (Bloom et al, 2013;Dakwar et al, 2011;Miller et al, 2000aMiller et al, , 2000bMitchell, 1999;Oquendo et al, 2004;Patterson et al, 2018;Poorolajal and Darvishi, 2016). Furthermore, aggression, impulsivity, and poor sleep are risk factors for suicidal behavior (Carli et al, 2010;Goldstein et al, 2008;Melhem et al, 2007;Nock and Kessler, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…The biologic mechanism for the effect of sleep duration on CVH has multiple pathways. Sleep duration is independently associated with several CVH metrics, such as weight status and hypertension, and with insulin sensitivity, which can lead to type 2 diabetes (5,6,28). Poor sleep may also lead to changes in behavioral components such as increased frequency of smoking or decreased physical activity (29).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 One longitudinal study that followed substance naïve adolescents into early adulthood found that erratic sleep patterns predicted smoking initiation. 4 In adults, transitioning from “adequate” to “inadequate” sleep duration over a period of 5 years predicted heavier smoking 5 and preexisting insomnia symptoms increased the likelihood of relapse after an attempt to quit smoking. 6 Chronotype—being a “morning” versus an “evening” person—has also been linked to smoking such that smokers are more likely to be an evening person.…”
Section: Introductionmentioning
confidence: 99%